Cobalt(iii)porphyrin to target G-quadruplex DNA. Issue 8 (9th January 2015) - Sabater, Laurent; Fang, Pei-Ju; Chang, Chi-Fon; De Rache, Aurore; Prado, Enora; Dejeu, Jérôme; Garofalo, Antonio; Lin, Jung-Hsin; Mergny, Jean-Louis; Defrancq, Eric; Pratviel, Geneviève
Abstract : A bulky cationic cobalt(iii ) porphyrin carrying two water molecules as axial ligands interacts in a π-stacking like mode with the 5′-external guanine quartet of G-quadruplex DNA. Abstract : G-quadruplex DNA ligands attract much attention because of their potential use in biology. Indeed they may interfere with G-quadrulex nucleic acid function in cells. Most of the G-quadruplex ligands so far reported (including also metal complexes) are large planar aromatic compounds that interact by π–π stacking with an external G-quartet of quadruplex. Porphyrins are well-known G-quadruplex ligands. We report herein a new porphyrin scaffold ( meso -tetrakis(4-( N -methyl-pyridinium-2-yl)phenyl)porphyrin) able to strongly and selectively bind to G-quadruplex DNA. We show that even when this porphyrin is metallated with cobalt(iii ), i.e. it carries two water molecules as axial ligands on the cobalt ion, on each face of the porphyrin, the interaction occurs by a π-stacking-like mode with an external G-quartet of quadruplex DNA.